THE IDEA OF LIBERATION IN RAMAYANA - Manickam, Thomas (Journal of Dharma, 1997)
"As long as the mountains stand and the rivers flow, so long shall the Ramayana be cherished among men and save them from sin.") This is a benediction given by Bhrama to Valmiki, the adikavi, the composer of the first Epic of India. In the invocation to Brahma this benediction is narrated by Valmiki and repeated by every redactor of Ramayana. The last phrase, "save them from sin" seems to be the central message of Valmiki’s Ramayana. But what about the central messages of other Ramayanas which have sprung up from the core material of Valmiki’s Ramayana? This article is probing into that aspect too.